Determination of The Antimicrobial, Antioxidant and Cytotoxic Activity of Paulownia tomentosa Steud - Inci, Sule; Dalkilic, Lutfiye Kadioglu; Kirbag, Sevda; Dalkilic, Semih (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2021)
Paulownia tomentosa, used in traditional Chinese medicine, is used in the treatment of diseases such as bronchitis and asthma thanks to its biological activities. In addition, it is known to have antimicrobial, antioxidant, anticancer effects and it is also used in the treatment of diseases such as dysentery, gonorrhea, hemorrhoids. In this study, the antimicrobial activity of extracts obtained from methanol solvent of flower and petal parts of P. tomentosa was determined according to the disk diffusion method. The antioxidant activity of the different concentrations of the extracts obtained from methanol solvent of flower and petal extracts was determined via the 2,2-diphenyl-1-picrilhydrazyl (DPPH) radical scavenging capacity method. Anticancer activity of different concentrations of extracts obtained from solvents such as methanol, ethanol and hexane was determined using the 3- (4,5-dimethylthiazole-2-yl) -2,5-diphenyl tetrazolium bromide (MTT) test method. As a result, it was found that methanol extract of the flower part of P. tomentosa showed the best antimicrobial activity against S. aureus (18 mm). It was determined that antioxidant activity of P. tomentosa increased depend to increasing concentrations. It was concluded that P. tomentosa has the best cytotoxic effect in hexane extract.
Keywords: Medical Plant; Paulownia tomentosa; Antimicrobial effect; Antioxidant effect